Screw dynamo in a torus - Stepanov, Rodion Alexandrovich; Chupin, Anton Viktorovich; Frick, Petr Gotlobovich (Computational Continuum Mechanics, 2008)
The problem of magnetic field generation under screw motion in a torus is studied numerically. It is shown that under periodicity requirement the solution for a thin torus coincides with the known solution for screw - dynamos in a cylinder. For a thick torus, a principally new solution to the screw dynamo problem is obtained. In this case the arising global magnetic field does not decay on the external torus axis and has the scale of a maximal geometrical size of the torus